2015
DOI: 10.1002/pds.3906
|View full text |Cite
|
Sign up to set email alerts
|

Trends in rates of acetaminophen‐related adverse events in the United States

Abstract: Purpose-The goal of this study is to summarize trends in rates of adverse events attributable to acetaminophen use, including hepatotoxicity and mortality.Methods-A comprehensive analysis of data from three national surveillance systems estimated rates of acetaminophen-related events identified in different settings, including calls to poison centers (2008-2012), emergency department visits (2004-2012), and inpatient hospitalizations (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 22 publications
(30 reference statements)
2
36
0
1
Order By: Relevance
“…2,3 Because of its over-the-counter availability and frequent use, intentional and unintentional paracetamol overdosing is common in clinical practice, and paracetamol-induced liver failure is indeed the leading cause of liver transplantations in the United States. 1,4 Zhou and colleagues recently investigated the frequency of unintentional paracetamol overdosing in a tertiary care hospital and reported that 6Á6% of paracetamol users exceeded the recommended maximum dose of 4 g/day. 5 Civan et al performed a similar analysis and reported overdosing in 2Á6%.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…2,3 Because of its over-the-counter availability and frequent use, intentional and unintentional paracetamol overdosing is common in clinical practice, and paracetamol-induced liver failure is indeed the leading cause of liver transplantations in the United States. 1,4 Zhou and colleagues recently investigated the frequency of unintentional paracetamol overdosing in a tertiary care hospital and reported that 6Á6% of paracetamol users exceeded the recommended maximum dose of 4 g/day. 5 Civan et al performed a similar analysis and reported overdosing in 2Á6%.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Un estudio realizado en Chile documentó que las intoxicaciones por medicamentos corresponden al 0,5% del total de admisiones en los servicios de urgencias, y de ellas, el 6,8% son debidas a intoxicación por acetaminofén (9,10), es decir, la frecuencia de la intoxicación se presenta de manera similar en Chile y Estados Unidos.…”
Section: Epidemiologíaunclassified
“…In this issue of PDS, Major et al report their analysis of three data sets to assess trends in acetaminophen events and liver injury from 2009 to 2012 . They found a decrease in the number of events during the study period in two categories: poison center cases and acetaminophen‐related hospitalizations, and an increase in emergency department visits.…”
Section: Editorialmentioning
confidence: 99%